Effects of corn gluten feed substituting soy bean meal on performance of Boer goats - Smither, Hunter L.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
With this study comes a hope to build information for the growing goat industry, and to establish better formulation combinations for producers. This study was concerned with the impact of substituting corn gluten feed (CGF) or corn dried distillers grains with solubles (DDGS) for soybean meal (SBM) in the growth performance of crossbred Boer goats. Seventy-five Boer type goats (26.9±0.2kg, approximately 70 days of age) were used in a completely randomized design with three goats per pens, with five pens per treatment, with pens being the experimental unit. Goats were fed for 35 d, along with feeders and goats being weighed weekly for effects on ADG, ADFI, G:F. The five treatments varied in ingredients used as the protein source but were isocaloric, isonitrogenous. Treatments were, 1) soybean meal; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF. The GLIMMIX procedure of SAS (v. 9.4, Cary, NC) was used to analyze data with an alpha value of 0.05. No impact of diet was detected on BW, ADG, ADFI, G:F (P < 0.05). It was discovered that feed costs between SBM or corn co-products as the protein source varied by $0.04/kg. This led to goats being fed corn co-products having lower (P = 0.0008) feed costs/goat during the 35-d experiment. However, feed cost per kg of gain did not differ (P = 0.941) among treatments. In conclusion, no difference was determined other than costs between the SBM control and CGF/ DDGS substitution. Therefore, these results suggest CGF or DDGS can completely substitute SBM in the diet of Boer type goats in a cost-effective manner, with no detected impacted on growth performance.
Keywords: Spring 2019